Association between strength with day sleepiness in individuals with Parkinson's disease - Sacha Clael; Camila Wells; Raphael Olegário; Sandro Nobre Chaves; Elaine Brandão; Liana Caland; Márcio Mota Rabelo; Lídia Bezerra (Universidade Federal de Santa Catarina, 2020)
The aim of this study is to analyze if there is an association between excessive daytime sleepiness with muscle strength in people with Parkinson's disease. This study is a cross-sectional study, with a quantitative approach. A total of 29 individuals with Parkinson's disease were recruited and classified in one of four stages of the modified Hoehn and Yahr scale. To assess the excessive daytime sleepiness the Epworth Sleepiness scale was used. The muscle strength was assess with handgrip and isokinetic dynamometers. There are non-significant correlation between Epworth Sleepiness scale with muscle strength, p < 0.05 and rho < 0.3. The muscle strength assessed by handgrip and isokinetic dynamometers does not associated with excessive daytime sleepiness assessed by Epworth Sleepiness scale.